The actuality of Freirian Pedagogy: continuing the speech, educators (Research, Society and Development, 2022)
The present research analyzes the actuality of Freirean Pedagogy, observing if and how it permeates the pedagogical practices of teachers of basic education in Limoeiro do Norte municipality, Ceará. This study follows a qualitative approach of the descriptive-exploratory type, in a field study format. As a data collection technique, we used the interview, carried out by Google Forms, with nine educators who work in basic education. When organizing and analyzing the speeches of the interviewees about their pedagogical practice, we identified in their reports a mention of Liberating Pedagogy, expressed in categories such as do-discence, humanization, dialogue, praxis and liberation. In the experiences presented, whether punctual or more commonplace, Freire's relevance and actuality in the school context is pointed out, whether from a reflective dialogue about the context with a view to awareness and consequent praxis and liberation, or through the dialogic teacher-teacher relationship. student with a view to social transformation. In theory, we realize that bringing Liberating Pedagogy to the classroom floor presupposes a movement that takes place outside it, especially in the field of public policies. Thus, in an educational context steeped in educational reforms and large-scale assessments that place quantity over quality, in a banking, vertical and reproductive way, Freire's motivational initiatives in the school environment are, in short, counter-hegemonic. Therefore, we hope that this research subsidizes the rescue of the present day of Liberating Pedagogy in the current context.